2011
DOI: 10.1007/s00586-011-2016-y
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of surgical, general and follow-up complications in lumbar spinal stenosis relative to patient age as emerged from the Spine Tango Registry

Abstract: Introduction Published opinions regarding the outcomes and complications in older patients have a broad spectrum and there is a disagreement whether surgery in older patients entails a higher risk. Therefore this study examines the risk of surgery for lumbar spinal stenosis relative to age in the pooled data set of the Spine Tango registry. Materials and methods Between May 2005 and February 2010 the database query resulted in 1,764 patients. The patients were subdivided into three socio-economically relevant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 28 publications
0
43
0
5
Order By: Relevance
“…Our results further suggest that higher rates of surgery are not necessarily worse and that the lowest surgical rates may be associated with worse average outcomes. Prior European research based on Spine Tango, the international spine registry of Eurospine, the Spine Society of Europe reported 1 year good or excellent global outcome after surgery between 62 % (patient-rated) and 80 % (surgeon-rated) [29][30][31]. Outcome was measured by the Core Outcome Measures Index (COMI) questionnaire consisting of validated questions covering the domains of pain, function, symptomspecific well-being, general quality of life, and social and work disability.…”
Section: Resultsmentioning
confidence: 99%
“…Our results further suggest that higher rates of surgery are not necessarily worse and that the lowest surgical rates may be associated with worse average outcomes. Prior European research based on Spine Tango, the international spine registry of Eurospine, the Spine Society of Europe reported 1 year good or excellent global outcome after surgery between 62 % (patient-rated) and 80 % (surgeon-rated) [29][30][31]. Outcome was measured by the Core Outcome Measures Index (COMI) questionnaire consisting of validated questions covering the domains of pain, function, symptomspecific well-being, general quality of life, and social and work disability.…”
Section: Resultsmentioning
confidence: 99%
“…12 Perhaps more importantly, the Spine Tango Registry has been effective in risk-adjusted benchmarking, assessing complications data, and documenting the overall effectiveness of surgery for common spinal conditions such as lumbar spinal stenosis. 13 Performing comparisons between treatment strategies using registries requires complex statistical methods designed to adjust for differences between treatment groups. 1 Nevertheless, registries are useful for monitoring the effectiveness of interventions, documenting complication rates, and assessing our ability to identify "whom to treat."…”
Section: Spinal Registriesmentioning
confidence: 99%
“…18 Sobottke et al not only documented complication rates following surgery for a lumbar degenerative condition (spinal stenosis), but found that older age was a predictor for developing a medical complication, but not for the development of a surgical complication. 13 Lee et al carefully documented complications from 1745 patients enrolled in a spine registry at the University of Washington and was able to provide risk adjustment analysis by including surgical invasiveness and other factors that are difficult to obtain from administrative databases, including the national inpatient sample. 9 …”
Section: Complicationsmentioning
confidence: 99%
“…The spinal surgical community is now starting to get the benefits of the development of Registries, and the paper by Sobottke [49] using data from the Spine Tango registry is a good example. It reviews the complications of operating on patients with spinal stenosis, and assessing their relation to age in 1,764 patients in the registry operated upon between 2005 and 2010.…”
Section: Spinal Stenosismentioning
confidence: 99%